Celestial Democracies - Kiss, Sándor (Hungarian Journal of English and American Studies, 2021)
Book review:Tamás, Nyirkos. The Tyranny of the Majority. New York: Routledge, 2018. vi + 154 pages. ISBN 978-1-351-21142-0. E-book. $56.20